Expiration-day effects of index futures in a frontier market: The case of Ho Chi Minh Stock Exchange - Nguyen Thi Kim Anh; Loc Dong Truong; H. S. Friday (International Journal of Financial Studies, 2022)
This study employs OLS, GARCH and EGARCH regression models to test the expiration-day effects of index stock futures on market returns, volatility and trading volume for the Ho Chi Minh Stock Exchange (HOSE). Data used in this study is from a daily return series of the VN30-Index for the period from 10August 2017 through 30 June 2020. The results derived from GARCH(1,1) and EGARCH(1,1) models consistently confirm that Index futures expiration-day effects on market returns exists in the HOSE. Specifically, the average market return for expiration days is significantly lower than other trading days, by 0.13% at the 5% level of significance. However, the results obtained from the regression models indicate that the expiration-day has no impact on market volatility and trading volume.
Keywords: 330; HOSE; index futures expiration-day effects; market returns; market volatility; trading volume